Surat Edaran Menag Nomor 05 Tahun 2022 dalam Perspektif Islam Wasathiyah: Analisis Fungsi Toa, dan Pendapat Ulama - Alam An Shori (Program Studi Aqidah dan Filsafat Islam, 2023)
The Minister of Religious Affairs Circular Letter No. 05/2022 regarding guidelines for the use of loudspeakers in mosques and prayer rooms has attracted attention from various groups, including representatives of the people. This study aims to: (1) Understand the definition of